ChemInform Abstract: A Practical Synthesis of 5‐Functionalized Thieno[2, 3‐d]pyrimidines. Issue 44 (15th October 2015) - Wilding, Birgit; Faschauner, Stefan; Klempier, Norbert
Abstract The synthesis of the title compounds is based on the condensation of thiophenes (I) and (IV) with formamide.